Educación para el emprendimiento en la universidad (Estudios) - Vásquez, César (2017)
The panorama of the innovative projection of the university, in function of the development of entrepreneurship, demands an understanding of all the theoretical - methodological perspectives that turn on their conceptualization and praxis. This article analyzes the problems of entrepreneurship and its educational implications, with the purpose of laying the theoretical-conceptual foundations for the formative orientation of its content and its implementation in higher education institutions.